Analisis Model Jembatan Bentang Akibat Beban Gempa - . Suyadi (UNIVERSITAS LAMPUNG, 2012)
In accordance the standard bridges, seismic loads must be taken into account in the combinationof loading conditions. Often the continous bridge model is a choise, especially on the model ofbridges with spans of more than 1 (one). This analysis focused on the piers of a bridge that consitsof 5 (five) spans. The variable in this model is layout of continous or simple beam. In this analysismade 5 (five) types of the bridge. To obtain the optimal and accurate design, use a dynamicanalysis by response spectrum based on the PGA value in SNI 03-1726-2002. With the pushovermethod using SAP 2000 software will be acquired and the value of Demand and CapacityDisplacement, so can to know the feasibility on the piers of a bridge modeled. Results of analysisthat only model IV incapable supporting the magnitude of longitudinal displacement. As for thetransverse direction of all the models capable to hold the magnitude of transverse displacement.Ductility of pier P1 and P2 for all models meet the requirements of the maximum ductility μD ≤ 5for multiple piers. Overall, the optmum behavior performance to resist earthquake loads is themodel II.